A molecular survey of tick-borne pathogens (Anaplasma and Ehrlichia spp.) in animal and tick samples in Malaysia / Koh Fui Xian - Koh, Fui Xian (2018)
Anaplasmosis and ehrlichiosis are tick-borne diseases which are caused by Gramnegative obligate intracellular bacteria in the family Anaplasmataceae. The diseases have been reported in a wide variety of wild and domestic animals from different parts of the world. Little data is available on the prevalence and transmission of the diseases in Malaysia. In this study, the occurrences of Anaplasma spp. and Ehrlichia spp. in animal and tick samples derived from different sources were determined. A total of 304 blood samples collected from livestock farms (cattle, sheep and goats) and 393 various animal blood samples provided by researchers from Veterinary Research Institute, Malaysia and Department of Wildlife and National Parks (PERHILITAN) Peninsular Malaysia from 2013-2014 for health screening were included in this investigation. A wide variety of ticks collected from livestock farms, aboriginal villages and the forest areas were subjected to morphological identification and molecular analysis of tick mitochondrial 16S rRNA gene to assist tick identification. Haemaphysalis and Dermacentor ticks were the main ticks identified in this study, besides Amblyomma and Rhipicephalus ticks. Using specific polymerase chain reaction (PCR) assays, Anaplasma DNA was detected in 136 (60.7%) cattle and 32 (80.0%) sheep from livestock farms investigated in this study. Majority of the Anaplasma spp. detected from the cattle were Anaplasma marginale, while all goats were not infected by Anaplasma spp. Anaplasma bovis DNA was detected from both wild and domestic animals in this study. A novel Anaplasma sp. tentatively designated as Candidatus Anaplasma pangolinii was detected from three of 15 pangolins (Manis javanica) investigated in this study. Both Ehrlichia canis and Anaplasma phagocytophilum were detected in dog blood samples and Rhipicephalus sanguineus ticks. A. phagocytophilum was mainly detected in questing ticks from the forest areas. A total of 61.5% ticks infesting livestock animals (cattle and sheep), 28.8% ticks collected from vegetation and small animals in the forest areas and 37.0% ticks iv infesting peri-domestic animals in aboriginal villages were PCR-positive for Anaplasmataceae DNA. Sequence analyses of the bacterial 16S rRNA gene region (238 bp) provided the identification for A. marginale, A. bovis, A. phagocytophilum, Anaplasma platys, Anaplasma spp. and Ehrlichia spp. in ticks and animal blood samples. New sequence variants of Anaplasma spp., Ehrlichia sp. strain EBm52, Ehrlichia mineirensis and Candidatus Ehrlichia shimanensis were identified in this study. In conclusion, the high detection rates of A. marginale in cattle blood samples may affect the livestock production in the cattle farms. The detection of Anaplasma spp. and Ehrlichia spp. in questing ticks and ticks infesting domestic and wildlife animals may pose a risk to human who come into contact with ticks or tick-infested animals. This study reports for the first time the type and distribution of various Anaplasma spp. and Ehrlichia spp. in animals and ticks present in this region. Further investigation should be carried out on the potential role of various tick species and the transmission dynamics of anaplasmosis and ehrlichiosis. Appropriate measures should be instituted for prevention and control of tick-borne diseases in Malaysia.